Productivity Analysis of Raisebore RB-50X for Raise Slot Drilling at Extraction level GBC PT. Freeport Indonesia - R J Kakisina; Yudho Dwi Galih Cahyono (Journal of Earth and Marine Technology (JEMT), 2021)
PT Freeport Indonesia is the largest gold and copper mine in Indonesia, located in Mimika Regency, Papua Province. In its operation, PT. Freeport Indonesia applies two mining systems, namely open pit mining and underground mining. Underground Mine at PT. Freeport Indonesia consists of DOZ, Big Gosan, DMLZ, Kucing Liar, and GBC, with one of the methods applied by PT. Freeport Indonesia is a block caving method. The Grasberg Block Cave mine has entered the production stage since September 2018, but in its operation the GBC Mine is still developing its operational area to meet production targets (development). The development cycle (cycle development), which is the main operation carried out, namely drilling and blasting, loading transporting (mucking hauling), primary support, and secondary support. To support the main operations, it is necessary to have main support consisting of access and area, ventilation, water and water, electricity, pull of tests, surveys, and dewatering. In the blasting process at the drawbell, one free face is needed which functions as the direction of rock collapsing in the blasting process on the drawbell. Making free face or commonly known as slot raise using a rasiebore machine from PT. Redpath for slot raise drilling. Meanwhile, in the drilling stage, the slot raise has a problem that has resulted in delays in the drilling process for the RB-50X raisebore tool. The impact of the delay in making the slot raise resulted in not achieving the production target due to a delay in the blasting process, where the blasting process in the drawbell area functions to break the rock so that it falls and can be transported to the crusher to enter the rock sizing process.